2012
DOI: 10.1073/pnas.1205995109
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of fatty acid synthesis and glycolysis in non-Hodgkin lymphoma

Abstract: The metabolic differences between B-NHL and primary human B cells are poorly understood. Among human B-cell non-Hodgkin lymphomas (B-NHL), primary effusion lymphoma (PEL) is a unique subset that is linked to infection with Kaposi's sarcoma-associated herpesvirus (KSHV). We report that the metabolic profiles of primary B cells are significantly different from that of PEL. Compared with primary B cells, both aerobic glycolysis and fatty acid synthesis (FAS) are up-regulated in PEL and other types of nonviral B-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
133
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(145 citation statements)
references
References 36 publications
(34 reference statements)
7
133
0
Order By: Relevance
“…Interestingly, the inhibition of AKT with miltefosine and perifosine, two alkylphospholipids, inhibited PEL cell growth, induced apoptosis in vitro, and delayed PEL tumor progression in vivo (72,73). Altogether, these studies indicated that ANG could also be protecting the PEL cells from apoptosis in part through the regulation of crucial antiapoptotic pathways, such as NF-B and AKT.…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, the inhibition of AKT with miltefosine and perifosine, two alkylphospholipids, inhibited PEL cell growth, induced apoptosis in vitro, and delayed PEL tumor progression in vivo (72,73). Altogether, these studies indicated that ANG could also be protecting the PEL cells from apoptosis in part through the regulation of crucial antiapoptotic pathways, such as NF-B and AKT.…”
Section: Discussionmentioning
confidence: 73%
“…Fresh medium was added, and cells were grown for an additional 24 h. PBS-washed cells were detached by scraping and pelleted for analysis by Metabolon, Inc. (Durham, NC) as in Bhatt et al (23). Data are presented as relative measures of "scaled intensity" after normalization to protein and median scaling to 1.…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that regulation of lipid metabolism could be an important component of BaP anticancer activity given that abnormally rapid lipogenesis is considered to be a hallmark of most cancers (15,16). Elevated lipogenesis in tumor cells is at least partly caused by high rates of fatty acid biosynthesis (15)(16)(17)(18), a phenomenon also observed in hematologic malignancies (19,20). Enzymes that synthesize saturated fatty acids [acetyl CoA carboxylase 1 (ACC1) and fatty acid synthase (FASN)] and monounsaturated fatty acids [stearoyl CoA desaturase 1 (SCD1)] are often overexpressed in malignant cells, and selective inhibition of these enzymes exerts an anticancer effect in vitro (18,(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%